Instagram and its influence on the eating patterns of persons aged 18 to 35 years - Márquez, Dewy (2024)
The aim of this study was to investigate how the social network Instagram affects the eating habits of individuals aged 18 to 35 in Peru. We used a methodological approach that included a virtual questionnaire on Google Forms, which was sent to participants who agreed to collaborate. Participants were selected randomly, and inclusion and exclusion criteria were applied. The research was descriptive, observational, and cross-sectional. The data were analyzed using SPSS version 26.0, and we found that there was no significant relationship between following healthy lifestyle accounts on Instagram and the nutritional knowledge of the 296 participants. Additionally, we did not find significant differences in the perception of Instagram's influence among different age groups. Furthermore, we found that the participants' eating behaviors were largely healthy, with no notable influence from Instagram.